2018
DOI: 10.12688/f1000research.13995.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the management of malignant pheochromocytoma and paraganglioma: focus on tyrosine kinase and hypoxia-inducible factor inhibitors

Abstract: Inactivating mutations of the succinate dehydrogenase subunit B ( SDHB) gene and the subsequent stabilization and activation of the hypoxia-inducible factor 2-alpha (HIF2α) unit are recognized hallmarks associated with the development of metastatic pheochromocytomas and paragangliomas (MPPG). Despite this discovery, the development of systemic therapies for patients with MPPG has been very slow. The rarity of the disease, the lack of preclinical animal models, and the impracticable development of large clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
(65 reference statements)
1
30
0
1
Order By: Relevance
“…Few studies have tried to exploit the underlying molecular mechanisms viz. mutation in succinate dehydrogenase subunit B gene (SDHB) and activation of hypoxia‐inducible factor HIF2α and evaluated the role of tyrosine kinase inhibitors (TKIs) . The results so far have been mixed with a reported 57% response rate in case of Sunitinib which was, however, accompanied by a significant proportion of adverse effects and treatment discontinuation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have tried to exploit the underlying molecular mechanisms viz. mutation in succinate dehydrogenase subunit B gene (SDHB) and activation of hypoxia‐inducible factor HIF2α and evaluated the role of tyrosine kinase inhibitors (TKIs) . The results so far have been mixed with a reported 57% response rate in case of Sunitinib which was, however, accompanied by a significant proportion of adverse effects and treatment discontinuation .…”
Section: Discussionmentioning
confidence: 99%
“…The results so far have been mixed with a reported 57% response rate in case of Sunitinib which was, however, accompanied by a significant proportion of adverse effects and treatment discontinuation . New generation TKIs like cabozantinib are expected to cause lesser adverse effects but need to be investigated further . In this setting, an equivalent therapeutic efficacy coupled with better safety profile and quality of life could favour the use of PRRT over chemotherapy and I‐ 131 MIBG in advanced PPGLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several TKI's that been described in case reports, series or phase II trials, such as sunitinib, cabozantinib, lenvatinib, pazopanib, and axitinib. An excellent overview of existing data and forthcoming trials was recently published by Toledo and Jiminez . All TKIs inhibit angiogenesis, by inhibiting the activation of the VEGF receptor (VEGFR).…”
Section: Implications For Treatment Of Metastatic Pgl/pccmentioning
confidence: 99%
“…As a result, HIF inhibitors could be a potential therapy for patients with cluster I PHEO/PGL. Molecular studies have identified HIF-2α as one of the main oncogenic drivers of PHEOs/PGLs [44,[54][55][56].…”
Section: Hypoxia-inducible Factor (Hif) Inhibitorsmentioning
confidence: 99%